The metabolic footprint of aging in mice - Houtkooper, Riekelt H. (Nature Publishing Group, 2011)
Aging is characterized by a general decline in cellular function, which ultimately will affect whole body homeostasis. Although DNA damage and oxidative stress all contribute to aging, metabolic dysfunction is a common hallmark of aging at least in invertebrates. Since a comprehensive overview of metabolic changes in otherwise healthy aging mammals is lacking, we here compared metabolic parameters of young and 2 year old mice. We systemically integrated in vivo phenotyping with gene expression, biochemical analysis, and metabolomics, thereby identifying a distinguishing metabolic footprint of aging. Among the affected pathways in both liver and muscle we found glucose and fatty acid metabolism, and redox homeostasis. These alterations translated in decreased long chain acylcarnitines and increased free fatty acid levels and a marked reduction in various amino acids in the plasma of aged mice. As such, these metabolites serve as biomarkers for aging and healthspan.